Bordah Traditional Music as A Local Wisdom On Malay Society Wedding Ceremony Coastal North Labuhanbatu Regency - Hasanah, Lailatul; Suroso, Panji; Siburian, Esra (Grenek: Jurnal Seni Musik, 2020)
This  study  aims  to  determine  the  existence,  functions  and  values  of  local  wisdom  of traditional music at the wedding ceremony bordah coastal communities wither North Labuhan Batu Regency. The theory used is the theory that relate to research topics such as the theory of existence, the theory of functions, traditional music theory, the theory of the wedding ceremony and the theory of values Local Wisdom. This study uses qualitative descriptive method where the data is examined through the collection of data in the form of photographs and videos, scientific papers, as well as the expert opinion in the material based on the research topic. The results showed that the presence of traditional music bordah is a traditional art in the form of poetry, music, dance and customs, the wedding ceremony. Bordah displayed on Regent Cup Festival activities, Hagaf, Thanksgiving child's birth and circumcision ceremony. Bordah functions of traditional music as entertainment, as Iringin, means of communication, expression of gratitude, the continuity of culture and a means of self-expression.  Local  wisdom  values  bordah  traditional  music  at  the  wedding  ceremony coastal communities wither North Labuhan Batu district: religious values, the value of art, solidarity, tolerance, the value of harmony and peace, the value of modesty, the economic value and the value of education. Keywords : Existence, Function Music, Local Wisdom, Bordah.